Spectroscopic Studies, Thermal Behaviour and Ac Impedance Study of Chemically Synthesized Silver Doped Polyaniline / BaFe12O19 Polymer Composite - Vinay, K.; Shivakumar, K.; T Ravikiran, Y.; Revanasiddappa, M. (International Journal of Engineering and Technology, 2018)
The present work is a study of a.c impedance response and thermal behaviour of IPANI/Ag/BaFe12O19 (PAB) composites synthesized by in-situ oxidative interfacial polymerization using (NH4)2S2O8 as an oxidizing agent at 0-50C. The synthesized polymer compo- sites were examined by FT-IR, TGA-DTA and DSC techniques. The a.c conductivity properties of the composites were investigated in the frequency range varying from 5x101 â€“ 5x106 Hz at room temperature using HIOKI make 3532-50 LCR Hi-tester. FT-IR profiles confirm the formation of ferrite composite. The endothermic regions in the DTA pattern are consistent with the change regions in the TG curve. The Cole-Cole plots observed in the form of exact semi-circles clearly suggests the Debye-type relaxation mechanism present in these materials.Â Â